Association of Night Shifts with Hospital-Acquired Infections in Nurseries: A Review - Abdullah Mohammed Alshakhes et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Hospital-acquired infections (HAIs) pose significant risks to patient safety and healthcare outcomes, particularly in neonatal nurseries where vulnerable infants are cared for. The unique challenges associated with night shifts—including staff fatigue, reduced staffing, and compromised infection control practices—may increase the likelihood of HAIs in this setting. This review examines the relationship between night shifts and HAIs in neonatal nurseries, discussing contributing factors, evidence from current studies, and recommendations for mitigating infection risks. Enhanced staffing policies, fatigue management, and the adoption of innovative technologies are essential to improving neonatal care and reducing HAIs during night shifts. Keywords: Night Shifts, Hospital-Acquired Infections, Nurseries. Received Date: September 14, 2024 Accepted Date: October 12, 2024 Published Date: November 13, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/237